Application of shape memory alloys (SMA) as a retrofit and strengthening component on reinforced concrete columns: Review Paper. (April 2020) - Zulkifli, S N I; Mohd Hisbany, M H; Ismail, R; Zakwan, F A A; Hazrina, A; Ismail, Badrul N.; Rashid, R S M
Abstract: Concrete structure deterioration and design deficiencies are stated as serious problems that frequently occur in the construction industry. It may lead to the loss of strength, stiffness, durability, and ductility of the existing structure. Therefore, an immediate structural strengthening must be highly considered to improve and repair the structure performance due to which the structure may fail to serve its purpose. The aim of this paper is to provide review of the structure strengthening methods for reinforced concrete columns proposed by researchers in the past two decades. However, the scope of this review paper is limited only to reinforced concrete columns retrofit by using the material of shape memory alloy (SMA). At the end of this paper, a suitable SMA form will be proposed for the future direction of research into this strengthening method.